Fully Printed High-Performance n-Type Metal Oxide Thin-Film Transistors Utilizing Coffee-Ring Effect - Liang, Kun; Li, Dingwei; Ren, Huihui; Zhao, Momo; Wang, Hong; Ding, Mengfan; Xu, Guangwei; Zhao, Xiaolong; Long, Shibing; Zhu, Siyuan; Sheng, Pei; Li, Wenbin; et al. (Nano-Micro Letters, 2021)
Metal oxide thin-films transistors (TFTs) produced from solution-based printing techniques can lead to large-area electronics with low cost. However, the performance of current printed devices is inferior to those from vacuum-based methods due to poor film uniformity induced by the “coffee-ring” effect. Here, we report a novel approach to print high-performance indium tin oxide (ITO)-based TFTs and logic inverters by taking advantage of such notorious effect. ITO has high electrical conductivity and is generally used as an electrode material. However, by reducing the film thickness down to nanometers scale, the carrier concentration of ITO can be effectively reduced to enable new applications as active channels in transistors. The ultrathin (~10-nm-thick) ITO film in the center of the coffee-ring worked as semiconducting channels, while the thick ITO ridges (>18-nm-thick) served as the contact electrodes. The fully inkjet-printed ITO TFTs exhibited a high saturation mobility of 34.9 cm2 V−1 s−1 and a low subthreshold swing of 105 mV dec−1. In addition, the devices exhibited excellent electrical stability under positive bias illumination stress (PBIS, ΔVth = 0.31 V) and negative bias illuminaiton stress (NBIS, ΔVth = −0.29 V) after 10,000 s voltage bias tests. More remarkably, fully printed n-type metal–oxide–semiconductor (NMOS) inverter based on ITO TFTs exhibited an extremely high gain of 181 at a low-supply voltage of 3 V, promising for advanced electronics applications. Highlights: 1 Fully inkjet-printed transparent high-performance thin-film transistors (TFTs) with ultrathin indium tin oxide (ITO) as semiconducting channels were achieved. 2 The energy band alignment at ITO/Al2O3 channel/dielectric interface was investigated by in-depth spectroscopy analysis. 3 Fully printed n-type metal–oxide–semiconductor inverters based on ITO TFTs exhibited extremely high gain of 181 at a low-supply voltage of 3 V, promising for applications in advanced electronic devices and circuits.